1996
DOI: 10.1038/bjc.1996.166
|View full text |Cite
|
Sign up to set email alerts
|

Association of vascular endothelial growth factor expression with intratumoral microvessel density and tumour cell proliferation in human epidermoid lung carcinoma

Abstract: Vascular endothelial growth factor (VEGF) expression, vascularisation and tumour cell proliferation were analysed in 91 human epidermoid lung carcinomas using immunohistochemistry. A polyclonal anti-VEGF antibody was used for VEGF expression, a polyclonal antibody directed against human von Willebrand factor (factor VIII) to identify blood vessels and the proliferating cell nuclear antigen (PCNA) as a marker for proliferating cells. Positive staining for VEGF was obtained in 54 out of 91 cases (59%), the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
160
2
7

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(179 citation statements)
references
References 23 publications
10
160
2
7
Order By: Relevance
“…Recently, Mattern et al (1996) analysed a series of 91 epidermoid lung carcinomas and, apart from the different percentage of cancers expressing the VEGF protein, they found a statistical association between the MC and VEGF expression. They did not analyse the relation between p53 and VEGF, which appears to be strictly connected in the regulation of tumour angiogenesis.…”
Section: P53 and Vegf Expressionmentioning
confidence: 99%
“…Recently, Mattern et al (1996) analysed a series of 91 epidermoid lung carcinomas and, apart from the different percentage of cancers expressing the VEGF protein, they found a statistical association between the MC and VEGF expression. They did not analyse the relation between p53 and VEGF, which appears to be strictly connected in the regulation of tumour angiogenesis.…”
Section: P53 and Vegf Expressionmentioning
confidence: 99%
“…In this respect assays on breast tumours (Toi et al, 1994) and epidermoid lung carcinomas (Mattern et al, 1996) have demonstrated a correlation between VEGF expression and MVD measurements. Recent studies have indicated that measurement of intratumoral levels of VEGF may be useful in assessing the activity of tumour angiogenesis (Toi et al, 1996).…”
mentioning
confidence: 91%
“…VEGF has been reported to be synthesized and secreted by a variety of cultured tumour cells (Senger et al, 1986) and human solid tumours, such as brain tumours (Plate et al, 1992;Berkman et al, 1993;Samoto et al, 1995), lung cancers (Mattem et al, 1996), breast carcinomas , gastrointestinal tract adenocarcinomas (Brown et al, 1993a), renal and bladder carcinomas (Brown et al, 1993b;Takahashi et al, 1994) and epithelial ovarian carcinomas (Olson et al, 1994;Boocock et al, 1995;Abu-Jawdeh et al, 1996). Increased expression of VEGF has been suggested to be involved in tumorigenesis, metastasis and the production of malignant effusion via the enhancement of vascular permeability or angiogenesis Neufeld et al, al, 1994).…”
mentioning
confidence: 99%